1997
DOI: 10.2486/indhealth.35.533
|View full text |Cite
|
Sign up to set email alerts
|

Response to Psychological Test in Elderly Patients with Hand-Arm Vibration Syndrome and Healthy Controls.

Abstract: We investigated the parasympathetic nervous response to psychological test using heart rate variation (HRV) during deep breathing in elderly patients with hand-arm vibration syndrome and healthy controls. Average age (SD) of 16 patients with vibration-induced white finger (VWF), 13 patients without VWF and 12 healthy controls was 60.1 (2.8), 60.6 (4.2) and 58.8 (3.8), respectively. After an initial supine rest for 40 min, psychological test (Stroop color word test and mirror drawing test) was performed for 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Workers with hand-arm vibration syndrome showed decreased HF and LF components during rest when compared with healthy workers 31) . In addition, SDNN and RMSSD decreased in workers with hand-arm vibration syndrome without vibration-induced white finger 32) . Hand-transmitted vibration may also cause persistent damage to nerves and blood vessels in the upper limbs or the higher centers of the autonomic nervous system.…”
Section: Vibrationmentioning
confidence: 98%
See 1 more Smart Citation
“…Workers with hand-arm vibration syndrome showed decreased HF and LF components during rest when compared with healthy workers 31) . In addition, SDNN and RMSSD decreased in workers with hand-arm vibration syndrome without vibration-induced white finger 32) . Hand-transmitted vibration may also cause persistent damage to nerves and blood vessels in the upper limbs or the higher centers of the autonomic nervous system.…”
Section: Vibrationmentioning
confidence: 98%
“…Laskar et al reported that workers with hand-arm vibration syndrome showed significantly decreased HF and LF components during rest 31) and significantly decreased SDNN and RMSSD during rest after a psychological test when compared with the healthy controls 32) . Among operators with vibration-induced white finger, the LF/HF ratio increased significantly during immersion of the hand in cold water at 10˚C, but did not increase in healthy controls 33) .…”
Section: Vibrationmentioning
confidence: 99%
“…The frequency-domain analysis of HRV has been used recently [1,34]. There are several reports on HRV in HAVS patients using time-domain analysis [2,12,13,14,15,19,22,36], whereas only two reports of frequency-domain analysis are available [17,27].…”
Section: Introductionmentioning
confidence: 99%